Perbandingan Efektivitas Flipchart Dan Podcast Sebagai Media Edukasi Gizi 1000 HPK Di Desa Tambakbaya Banten - Azzahra Rahmaprilia Danisfa; Desiani Rizki Purwaningtyas (Madu Jurnal Ilmu Kebidanan, 2026)
Improving nutrition-related knowledge and attitudes among women of reproductive age regarding the First 1,000 Days of Life (1,000 Days) is essential as an early strategy for preventing stunting. The effectiveness of nutrition education is influenced by the educational media used. Therefore, this study aimed to analyze and compare the effectiveness of flipcharts and podcasts as media for nutrition education on the First 1,000 Days of Life in improving nutrition knowledge and attitudes among women of reproductive age in rural areas. This quasi-experimental study employed a pretest–posttest control group design and was conducted in Tambakbaya Village, Lebak Regency, Banten, Indonesia. A total of 106 women aged 15–35 years participated and were assigned to either the flipchart group or the podcast group. Nutrition education was delivered in three sessions. Data were analyzed using the Mann–Whitney and Wilcoxon tests. Prior to the intervention, most subjects had poor nutrition knowledge. Following the intervention, the majority demonstrated fair to good levels of nutrition knowledge. Positive attitudes toward nutrition predominated both before and after the intervention. Nutrition education on the First 1,000 Days of Life delivered through both flipcharts and podcasts significantly improved nutrition knowledge and attitudes. However, flipchart-based education resulted in greater improvement in nutrition knowledge than podcast-based education. These findings highlight the importance of selecting educational media that align with the characteristics of the target population.